Robert Fudali - (nie)zwykły człowiek = Robert Fudali - (Extra)ordinary man - Fudali, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article was written on the sixth anniversary of the death of Robert Fudali, a longtime employee of the University of Zielona Góra. It was written on the basis of the memories of several people who knew him, who was friends with him or collaborated with him creating his natural habitat (colleagues, friends, associates, students). Robert Fudali's silhouette has been portrayed in many aspects: what kind of human he was, what hobbies he had and what he was passionate about, his research interests, him as a teacher, and what he left behind. Memories mainly concern the period in which he was associated with the Wyższa Szkoła Pedagogiczna in Zielona Góra and later the University of Zielona Góra.
Keywords: Fudali, Robert (1961-2011); biografia; pedagodzy; Uniwersytet Zielonogórski; biography; University of Zielona Góra